Hvilken virkelighed? Hvis virkelighed? Et seminar om research som basis for den dramatiske tekst - Branth, Janicke (Peripeti, 2021)
In this short article about the seminar on research and drama held at the Theatre of Aarhus in september 2007, Janicke Branth presents a series of thoughts on the relationship between art and reality in contemporary theatre.